Biological characteristics of Indo-Pacific King Mackerel (Scomberomorus guttatus, Bloch and Schneider 1801) in Moro Waters part of Kepulauan Riau, Indonesia. (July 2018) - Noegroho, T; Boer, M; Adrianto, L; Sulistiono,
Abstract: Research related to biological characteristics of Indo-Pacific King Mackerel in Indonesia is still rare, whereas fishing activity has been carried out. The study was conducted from 2014-2017 in Moro Waters, Riau Islands, Indonesia. The purpose of this study was to analyze the biological characteristics including length frequency, length weight relationship, Gonado Maturity Stages, Gonado Somatic Index (GSI), sex ratio, length at first maturity, fecundity and ova diameter. From length frequency were obtained mode size at 37-39 cm for male, 52-54 cm for female and 43-45 cm for transition sex. The growth pattern of king mackerel was isometric. The gonad fish were dominated of mature gonads by 52%, and the immature gonads by 48%, with level V was almost found every month. GSI shows that spawning season in January-August and peak season occurs in April-May. The results of chi-square test showed that there were significant differences number of males and females fish. The length at first maturity was at 47, 4 cm, in the range between 46.3 to 48.5 cm. The fecundity ranged on 28.082-1.506.075 eggs, on a length of 45-55 cm. Based on the development of the ova diameter and Gonad Maturity Stage, the King Mackerel spawning pattern is partial spawner.